Prion Diseases - Baker, Harry F.; Baker, Harry F.; Ridley, Rosalind M.; Ridley, Rosalind M. (Methods in Molecular Medicine,, 1996)
In Prion Diseases leading researchers and clinicians describe their state-of-the-art findings and hypotheses arising from a variety of different approaches to this group of diseases. Their approaches include clinical presentations, epidemiology, transgenic methods, and diagnostic tests via transmission electron microscopy and immunoblotting. The diseases covered include human and animal spongiform encephalopathies, such as Creutzfeldt-Jakob disease, mad cow disease, and scrapie. Prion Diseases illuminates the conflicting hypotheses that have evolved to explain these diverse disorders which can appear as infectious diseases a genetically determined diseases, as well as ones sharing neuropathological similarities with such common neurodegenerative diseases as Alzheimer's disease, Parkinson's disease, and amyotropic lateral sclerosis. It provides a much-needed overview of various approaches to understanding these diseases by showing how researchers have analyzed their different facets, ranging from the epidemiology of the human versions to molecular genetics of the animal forms of the diseases.